Challenges and Opportunities in Simulations and Computer Experiments in Industrial Statistics: An Industry 4.0 Perspective. Issue 2 (12th January 2021) - Kenett, Ron S.; Vicario, Grazia
Abstract: This paper is a review of the growing role of simulations and computer experiments in industrial statistics, with an emphasis on Industry 4.0 applications. It maps the background, the current state, and the future directions of computer simulations in a wide range of process engineering, product design, and analytic disciplines. Abstract : In Industry 4.0 applications, one sees a growing role of twinning a physical plant with simulation‐based surrogates. Simulating the behavior of a system is a cost‐efficient approach to knowledge building. The paper provides a review of simulation models and computer experiments, with a focus on Industry 4.0 applications.